Biomarkers of Gut Microbiota in Chronic Spontaneous Urticaria and Symptomatic Dermographism - Liu, Runqiu; Peng, Cong; Jing, Danrong; Xiao, Yangjian; Zhu, Wu; Zhao, Shuang; Zhang, Jianglin; Chen, Xiang; Li, Jie (Frontiers in Cellular and Infection Microbiology, 2021)
Background Chronic urticaria (CU) is a chronic inflammatory skin disease associated with Th2 immune response. The two most common subtypes of CU, i.e., chronic spontaneous urticaria and symptomatic dermographism (CSD), often coexist. However, the pathogenesis of CSD is still unclear. Gut microbiota plays an important role in immune-related inflammatory diseases. The purpose of this study was to explore the correlation between gut microbiota and CSD. Methods A case-control study was conducted on CSD patients as well as gender- and age-matched normal controls (NCs). The 16S ribosomal DNA sequencing of fecal samples was used to detect the gut microbiota of all subjects. QPCR was used to further verify the species with differences between the two groups. Results The alpha diversity of gut microbiota decreased in CSD patients, accompanied by significant changes of the structure of gut microbiota. Subdoligranulum and Ruminococcus bromii decreased significantly in CSD patients and had a potential diagnostic value for CSD according to receiver operating characteristic curve (ROC) analysis. Enterobacteriaceae and Klebsiella were found to be positively correlated with the duration of CSD, while Clostridium disporicum was positively correlated with the dermatology life quality index (DLQI). Conclusions The gut microbiota of CSD patients is imbalanced. Subdoligranulum and Ruminococcus bromii are the gut microbiota biomarkers in CSD.